Accuracy of timing in some time study methods - Pehkonen, Aarne (Agricultural and Food Science, 1978)
With measured times varying between 3 ... 115 cmin (average 19 cmin) the average deviation in the use of time study instruments (approximately 63 000 times) was 0,83 cmin (6,4 %). As the times became shorter, below 15 ... 20 cmin, there was a sharp decline in the relative measuring accuracy. The measuring accuracy improved when conditions at the study location were favourable to the observation of the break point or limited the reception of information other than that coming from the study object. The measuring accuracy of watches with pointer display improved if the pointer could be stopped at the moment of measuring and the result read out afterwards. The variables describing the characteristics of the test person, e.g. age, basic schooling, degree of training and intelligence, were correlated with the measuring accuracy. The measuring of times did not seem to require special techno-mechanical talent. With the aid of variables that describe the characteristics of the test persons and that can be determined in a simple manner it is not possible to give a reliable estimate as to how well a specific person is suited to the task of a time investigator. This problem may be solved by using, for example, a work test based on simulation.